2014
DOI: 10.1371/journal.ppat.1004045
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B Exits the Host Cell in Shed Microvesicles Displaying Autophagosomal Markers

Abstract: Coxsackievirus B3 (CVB3), a member of the picornavirus family and enterovirus genus, causes viral myocarditis, aseptic meningitis, and pancreatitis in humans. We genetically engineered a unique molecular marker, “fluorescent timer” protein, within our infectious CVB3 clone and isolated a high-titer recombinant viral stock (Timer-CVB3) following transfection in HeLa cells. “Fluorescent timer” protein undergoes slow conversion of fluorescence from green to red over time, and Timer-CVB3 can be utilized to track v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
294
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(312 citation statements)
references
References 64 publications
18
294
0
Order By: Relevance
“…Recent studies have brought increasing recognition to the fact that multiple members of the Picornaviridae are released from cells enclosed in membranous vesicles in the absence of cell lysis (2)(3)(4)(5)(6). This mode of cellular egress has been suggested to play an important role in disease pathogenesis by masking viral antigens from the immune system (2) or increasing the number of viral genomes delivered to single infected cells (6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have brought increasing recognition to the fact that multiple members of the Picornaviridae are released from cells enclosed in membranous vesicles in the absence of cell lysis (2)(3)(4)(5)(6). This mode of cellular egress has been suggested to play an important role in disease pathogenesis by masking viral antigens from the immune system (2) or increasing the number of viral genomes delivered to single infected cells (6).…”
Section: Discussionmentioning
confidence: 99%
“…Poliovirus and other enteroviruses appear to egress nonlytically from infected cells in autophagosome-derived vesicles containing LC3-II (4,5,28). These enteroviral vesicles are much larger than eHAV, and contain a much greater number of viral capsids than eHAV vesicles (2,6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though no molecular mechanism has been proposed, autophagosome interactions with the plasma membrane have been suggested to allow the release of virus particles (32) and the cell-to-cell transmission of Brucella (2). Recently, using a fluorescent timer approach, it was shown that the autophagic pathway contributes to the shedding of microvesicles that harbor infectious coxsackievirusB and contribute to the spreading of the virus from cell to cell (33).…”
Section: Discussionmentioning
confidence: 99%